Fatigue Behaviour of Mechanical Joints: A Review - Animesh Kumar Basak; Dharamvir Singh Bajwa; Alokesh Pramanik (Metals)
Mechanical joints, regardless of materials, are useful when joining multiple components, though there are certain limits when applying them in engineering applications such as fatigue loading. The purpose of this research is to provide a comprehensive review of the trend of fatigue properties of common non-thermal mechanical connections such as adhesive, bolted, clinched and riveted joints. Towards that, a narrative approach was taken. In modern engineering applications, most of the joints contain both metallic and non-metallic components. The relevant experimental studies have proven many factors that can affect each type of joint and how they can be implemented in real-time appliances. For instance, the fatigue behaviour of adhesive joints is affected by the bond length, thickness and the use of different materials. Increasing the bond length can enhance its fatigue resistance up to a certain length, whilst increasing the thickness of laminate or adhesive decreases the fatigue life unless the surface roughness increases. On the other hand, different laminate materials can affect the fatigue performance depending on their mechanical properties. These findings will allow readers to have an overall concept of the fatigue behaviour of mechanical joints and the influence of various internal and external parameters on that.